UNSUR SOSIAL BUDAYA DALAM SERAT ANGLINGDARMA - Masturoh, Titin (Acintya, 2014)
This research aims to find answers of the questions: (1) how the Serat Anglingdarma as the literarywork is; (2) how the Socio-Cultural Elements of Serat Anglingdarma are. Focus of this researchdiscusses about the text of Serat Anglingdarma, so the use of genetic structuralism approach to theanalysis of intrinsic and extrinsic elements are the elements of social culture.This result of the research shows that Serat Anglingdarma contains message that can function as thekingdom dynasty relationship and strengthening or authority at the time as a complementary chain ofgenealogical ancestors. Serat Anglingdarma as a literary work contains the important elements, theyare: (1) element of plot; (2) element of characterizing; (3) element of setting; (4) element of theme (themain theme and additional theme); (5) element of message. The social elements of Javanese culture inSerat Anglingdarma can be seen from the kinship system. It can also be seen from the language,because the language used in Serat Anglingdarma is Java krama and Java ngoko language. SeratAnglingdarma can be seen from the farm system containing the ways of farming. While viewed fromthe art, Karawitan is used for the ceremony and certain days.Keywords: Socio-cultural, Serat Anglingdarma, Javanese.